Are lung adenocarcinoma mutations shaping the immune microenvironment? - Rochigneux, Philippe; Garon, Edward B. (Translational Cancer Research, 2018)
Recently, Biton et al. published in Clinical Cancer Research the article “TP53, STK11 and EGFR Mutations Predict Tumor Immune Profile and the Response to anti-PD-1 in Lung Adenocarcinoma” (1). This article points out the challenging question of the interplay between tumoral mutations in lung adenocarcinoma (localized and metastatic) and the composition of immune microenvironment.